PERENCANAAN STRATEGIS PEMBANGUNAN KAMPUNG (DESA) - Syahputra, Syahputra; Rusli, Zaili; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Strategic Planning of Village Development (Village). This study aims to find out the development strategy of Kampung Sabak Auh Siak District. This research uses descriptive qualitative research method. Primary data is obtained directly from key informants, ie stakeholders or layers required by the researcher. Secondary data is obtained from research documents. In this study, the author uses SWOT analysis, namely internal factors about strength (Strength) and Weakness (weakness) and the results of analysis of external factors of opportunity (opportunity) and treatment (threats). The results of this study indicate some strategic planning that can be carried out, namely human resource development, community economy, health services and infrastructure development.